Experiments and simulations on the possibility of radiative contraction/collapse in the PF-1000 plasma focus - Mohamad, Akel; Cikhardt, Jakub; Kunze, Hans Joachim; Lee, S.; Paduch, Marion; Saw, S. H. (De Gruyter, 2016)
Experimental studies of discharges in the plasma focus facility with neon fi lling and respective numerical simulations employing the radiative Lee code are reported. The pinch currents exceed the Pease-Braginskii current, which indicates that radiative losses are larger than heating and that contraction of the formed plasma should occur. Both of these effects were indeed observed. Parallel numerical simulations were crucial for the identifi cation of such an effect.